Epigenetic regulation in pluripotent stem cells: a key to breaking the epigenetic barrier - Watanabe, Akira (The Royal Society, 2013)
The differentiation and reprogramming of cells are accompanied by drastic changes in the epigenetic profiles of cells. Waddington's classical model clearly describes how differentiating cells acquire their cell identity as the developmental potential of an individual cell population declines towards the terminally differentiated state. The recent discovery of induced pluripotent stem cells as well as of somatic cell nuclear transfer provided evidence that the process of differentiation can be reversed. The identity of somatic cells is strictly protected by an epigenetic barrier, and these cells acquire pluripotency by breaking the epigenetic barrier by reprogramming factors such as Oct3/4, Sox2, Klf4, Myc and LIN28. This review covers the current understanding of the spatio-temporal regulation of epigenetics in pluripotent and differentiated cells, and discusses how cells determine their identity and overcome the epigenetic barrier during the reprogramming process.